2020
DOI: 10.37934/arfmts.78.1.122136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Blade Angle on Aerodynamic Performance of Archimedes Spiral Wind Turbine

Abstract: Energy harvesting from wind in urban areas is an important solution to meet energy needs and environmental care. This study describes the effect of blade angle on the aerodynamic performance of small-scale Archimedes spiral-wind-turbine blades by computational simulation, which is experimentally validated. Archimedes wind turbine is classified as one of the HAWTs. The computational approach was used to predict the aerodynamic performance of the scaled-down rotor blades. Blade angle is defined by the angle betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…On the other hand, the ASHT achieved a Cp of 0.5515 at a TSR equal to 1.35 [5]. The maximum Cp is slightly higher than those with similar AST presented in the literature for wind applications [15,16,17,24,25,26]. It is evident that the Cp of the AST is lower than that of the ASHT.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…On the other hand, the ASHT achieved a Cp of 0.5515 at a TSR equal to 1.35 [5]. The maximum Cp is slightly higher than those with similar AST presented in the literature for wind applications [15,16,17,24,25,26]. It is evident that the Cp of the AST is lower than that of the ASHT.…”
Section: Resultsmentioning
confidence: 62%
“…For example, the behavior of the turbine has been compared for several blade inclination angles (γ) with respect to the axial axis. γ was fixed at several values, such as 50°, 55°, 60° and 65° [15]. In this case, the higher Cp was equal to 0.22 at a TSR of 1.71 with a γ of 50°.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key problem with in-pipe turbines is determining the appropriate design to maximize their efficiency. The performance of water turbines is studied by some researchers using computational fluid dynamics (CFD) while others also run experiments to learn more about the technology and mechanism of the system [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%

Impact of Different Blade Counts on In-Pipe Drag-Type Water Turbines

Nurul Amira Zainal,
Mohamad Nazaem Zabidi,
Mohd Suffian Ab Razak
et al. 2023
ARFMTS
“…By validating the experimental results and numerical simulations, they predicted the performance of the turbine to achieve high efficiency. In 2019, Maulana et al [17] experimentally studied an AST and found that the turbine efficiency has a nonlinear trend with increasing flow rate, and the maximum efficiency of the turbine occurs at an intermediate flow rate. In 2021, Bustomi et al [18] conducted an experimental investigation of a inclined axis turbine.…”
mentioning
confidence: 99%